An Introduction to Slow Money and its Gandhian Roots. (October 2014) - Ashta, Arvind
Slow money, or patient nurturing capital directly invested locally in small firms in food and basic industries, is a new term but an old notion. It gains revival in times of crisis, especially after the recent financial crisis, as people search for meaning and a way out of the ruinous effects of uncontrolled capitalism. This article traces the roots of the movement to Gandhian thought. It examines the cases of the CIGALES clubs of microangels in France and the more recent case of the slow money alliance to ferret out the basic principles and strategies of these movements and how they are aligned with Gandhian values.